2004
DOI: 10.1021/jf035341l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Aroma of a Wine from Maccabeo. Key Role Played by Compounds with Low Odor Activity Values

Abstract: An extract from a dry young wine from Maccabeo was studied by aroma extract dilution analysis (AEDA), quantitative gas chromatography, and different sensory studies. In a first study, 53 different aroma compounds were quantified and used to prepare aroma models. 2-Methyl-3-furanthiol (FD = 16) and 4-methyl-4-mercaptopentan-2-one (FD = 2), could not be quantified and were not included in those models, which were not very similar to the original wine. Omission tests did not show the existence of impact compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
218
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(242 citation statements)
references
References 32 publications
16
218
2
5
Order By: Relevance
“…Ethyl acetate, isoamyl formate, diethyl succinate and ethyl lactate were the major esters in the 27 samples. The fatty acid esters primarily contributed fruity aromas (Escudero et al, 2004), diethyl succinate contributed a fruity and sweet aroma (Fan and Qian, 2006), and isoamyl formate produced a mulberry aroma. These compounds may be important contributors to the aroma of the Chinese rice wine samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethyl acetate, isoamyl formate, diethyl succinate and ethyl lactate were the major esters in the 27 samples. The fatty acid esters primarily contributed fruity aromas (Escudero et al, 2004), diethyl succinate contributed a fruity and sweet aroma (Fan and Qian, 2006), and isoamyl formate produced a mulberry aroma. These compounds may be important contributors to the aroma of the Chinese rice wine samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, for some ethyl esters, such as ethyl hexanoate, ethyl octanoate, ethyl myristate, ethyl oleate and ethyl linoleate, there was a decrease with wine age, increasing as the excess fatty acid esters formed by yeast were hydrolyzed during the aging process (Escudero et al, 2004). The reduction of furfural to furfuryl alcohol (and further products) occurred during the aging process.…”
Section: Volatile Compounds In Chinese Rice Wines Based On Wine Agementioning
confidence: 99%
“…Finally, the relationship between perceived intensity and concentration at suprathreshold concentrations cannot be predicted from the threshold concentration (i.e., the slope of a plot of perceived intensity vs. concentration is different for different compounds). Because of these limitations, OAVs are not always good indicators of the contribution of individual odorants to the perceived intensity of a mixture (Audouin et al 2001), as further demonstrated with the white wine variety Maccabeo using reconstitution studies with a dearomatized white wine matrix and pure aroma compounds (Escudero et al 2004). Selected compounds such as fusel alcohols, acids, and esters, even when present at concentrations above their sensory thresholds, did not have a significant impact on the overall wine aroma.…”
Section: Gc-olfactometrymentioning
confidence: 97%
“…As previously discussed, much wine sensory research has focused on correlating descriptive sensory and quantitative analytical data in order to successfully identify odor compounds that contribute to the overall aroma perception of wine (Guth 1997a, 1997b, López et al 1999, Kotseridis and Baumes 2000, Lee and Noble 2003, Escudero et al 2004, Campo et al 2005, Bailly et al 2006, Benkwitz et al 2012. The use of sensory evaluation to elucidate the impact of complex aroma compound interactions, including masking and enhancing effects, is likely to improve our understanding of the perceived aroma of wine (Atanasova et al 2005a).…”
Section: Sensory Evaluation Of Winementioning
confidence: 99%
“…These compounds have usually low perception limits (few g L −1 ), however could have the higher impact on wine aroma properties [21,22]. E-␤-damascenone has odour descriptors of apple and sweet [23], and backed apple [24] and its OT in wines is 0.05 g L −1 [25]. All the wines analysed exhibited concentrations above its OT, suggesting the contribution of this compound to the wines aroma.…”
Section: 3mentioning
confidence: 98%